Work Engagement in the Context of Confucian Culture: A Case of Chinese Civil Servants - Lyu, Xiaojun (Frontiers in Psychology, 2020)
Although work engagement as a positive organizational behavior has gained considerable achievements in recent years, there is still a lack of content research based on certain culture, job and group characteristics. This study conducts a grounded theory research on work engagement by coding and analyzing the interview files from public servants working in the government located in Eastern China. The result shows a five-dimension construct of work engagement, which includes loyalty to the work, commitment to the working relationships, positive emotion, initiative action, and priority for mixed roles. Additionally, the current study also constructs a theoretical model which discovers the dynamic variables motivating the process of work engagement, and the influence of confucianism.